New methods to measure the built environment for human-scale travel research: Individual access corridor (IAC) analytics to better understand sustainable active travel choices - Appleyard, Bruce (Journal of Transport and Land Use, 2015)
While travel is an inherently linear activity, most studies rely on coarse zonal measures of the built environment, likely missing key details important to human-scale travelers (pedestrians and bicyclists). To more fully understand these relationships, this study tests a new, linear spatial unit of analysis (the individual access corridor) in combination with finer-grained geospatial data (parcel, point, street network)—in sum, human-scaled measures for human-scale travel research. This paper first analyzes the current state of practice, details the development of a set of new linear human-scaled measures, and finally, provides both a quantitative and qualitative assessment of their usefulness toward research and policy application. This paper confirms that these new measures both improve model performance and, perhaps more importantly, provide richer, more nuanced insight into the influence of the built environment on human-scale travel. For example, this study finds that smaller parcels, the presence of small personal-service retail opportunities, and narrower, well-connected streets are positively associated with walking and bicycling. Furthermore, this paper is one of the first to align built environment measures along an individual’s path, from origin to destination, as well as to provide a detailed examination of the choice of bicycle over other modes.